The Role of Boundary Spanner in Maintaining the Sustainability of Padang City Branding - Adona, Fitri; Nita, Sri; Yusnani, Yusnani (Economics, Business, Accounting & Society Review, 2023)
The lack focus on brand positioning and brand identity in Indonesia, especially in creative industries based on local uniqueness, reflects a lack of development and competitiveness. This research critically evaluates the sustainable development of Padang City city branding with a focus on the role of leaders as boundary spanners in maintaining the sustainability of city branding and building brand awareness. Although required to create uniqueness, Padang City Branding is still influenced by the previous city branding development discourse, causing a lack of specifications and similarities with other cities in West Sumatra. Although the majority of the population is Muslim, the concept of halal tourism has not been created well. This study aims to understand the role of leaders in each institution as boundary spanners in maintaining the sustainability of city branding. As boundary spanners, leaders in each institution are considered central in maintaining the existence of city branding and building efficient policy networks. Observation-participating research methods using the Internet assist researchers in interacting with boundary spanners and understanding culture from the perspectives of its members. This research yields in-depth insights into the leader's key role as a boundary spanner in the context of Padang City city branding.